Intimate partner violence against pregnant women: sociodemographic profile and characteristics of the aggressions - Naiane Beatriz da Silva; Rosely Erlach Goldman; Hugo Fernandes (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To identify the sociodemographic profile and the main characteristics of violence by intimate partners in pregnant women in São Paulo, Brazil. Method: Cross-sectional study based on notifications for suspected or confirmed cases of inter-police violence from the National Disease Notification System (SINAN) carried out in the 2016-2019 period. Collection was performed between March and June 2020. Chi-squared test or Fisher's Exact test were used in statistical analysis. Results: A total of 4,269 notifications were obtained and the prevalent profile was women between 20 and 34 years old (62.5%), brown or black (51.3%), who have completed high school (22.5%) in the first trimester of pregnancy (44.2%). Physical violence was more frequent (48.3%), occurred at home (59.1%), motivated by sexism (22.29%). Sexual violence or rape was more frequent (85.4%) with abortion in cases provided for by law (39%). Conclusion: Adult brown or black women in the first gestational trimester experienced physical violence more frequently.